Intercultural Communication And Social Resilience: Javanese Transmigrant Communities In Lampung - Setiabasith, Dzaki (KOMUNIKA, 2025)
This study explores the intercultural communication dynamics and social resilience among Javanese transmigrant descendants in Lampung experiencing return migration patterns. Drawing on qualitative interviews with 16 informants (2nd–4th generation) conducted in 2024, the study examines how intergenerational communication patterns, cultural transmission processes, and community communication networks shape their migration decisions and social resilience. The research employs the Communication Theory of Identity, Intercultural Communication Theory, and Community Communication frameworks to analyze the complex interplay between symbolic communication, place attachment, and social resilience. Findings reveal that intergenerational transmission of Javanese values such as gotong royong and unggah-ungguh occurs through multiple communication channels, including oral traditions, ritual practices, and digital media, strengthening symbolic identity while creating hybrid cultural expressions. Communication barriers emerge from language differences and generational gaps, yet informal community interactions and shared symbolic practices are pivotal in maintaining social resilience. The study highlights how transmigrant communities negotiate hybrid identities through strategic communication practices and a balance between staying rooted and moving away. These insights contribute to developing communication strategies to reinforce regional resilience and prevent involuntary outmigration.